The attention-based view: Review and conceptual extension towards situated attention - Christoph Brielmaier; Martin Friesl (International Journal of Management Reviews, 2022)
Over two decades ago, William Ocasio introduced the attention-based view (ABV) of the firm with a powerful argument: firm-level behaviour is the result of the situated distribution and allocation of managerial attention, embedded in broader organizational structures and the environmental context. ABV-based research has received substantial and increasing scholarly attention, resulting in a complex and incoherent body of research. In order to address this issue, this paper takes stock of extant research on the ABV and consolidates key debates. Based on a systematic review of 173 articles, we synthesize existing research into a unifying framework. Drawing on this framework, we propose situated attention as a central theme for future research. We elaborate on four situational factors (materiality, social dynamics, temporality and what we call framing of the strategic setting), which may influence how actors' attention is situated in the particular context.
Keywords: 650